Unveiling the Power of Collaboration: Collaborative Strategic Reading in Enhancing Undergraduate Reading Comprehension - Amumpuni, Rengganis Siwi; Hartono, Rudi; Rukmini, Dwi; Haryanti, Rahayu Puji (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
This study investigates the effects of Collaborative Strategic Reading (CSR) on undergraduate students’ reading comprehension. A convergent parallel mixed-methods design was employed, involving 30 purposively selected undergraduate students (11 males and 19 females, aged 18-20) enrolled in reading comprehension courses. Data were collected using reading comprehension tests and questionnaires, and were subsequently analyzed with SPSS to evaluate the impact of the CSR intervention. The results demonstrated a statistically significant improvement in students’ reading scores, as evidenced by a t-test result at the 0.05 significance level (p = 0.000 < 0.05). These findings confirm the effectiveness of CSR as an instructional strategy for enhancing reading comprehension. Students particularly commended CSR’s straightforward structure and ease of adaptation into the curriculum. Thus, the study concludes that CSR not only sharpens academic reading but also increases motivation to engage in reading. This study seeks to close the gap between theoretical research and practical teaching approaches, showcasing the need for the implementation of CSR in higher education.